2022
DOI: 10.2147/ahmt.s383872
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccination Uptake and Its Predictors Among Female Adolescents in Gulu Municipality, Northern Uganda

Abstract: Background: Human papillomavirus (HPV) is the putative case of cervical cancer. However, uptake of HPV vaccination is reportedly low in Uganda. This study explored the predictors of HPV vaccination uptake among female adolescents aged 15-18 years in Gulu Municipality, in northern Uganda. Methods: This was an analytical cross-sectional survey that was conducted among adolescents aged 15-18 years in Gulu Municipality. A structured questionnaire was used. Data were analyzed using Statistical Package for the Socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…This means the two Sub-Counties are way below the National target (80%). These findings are consistent with that found by Aruho et al (2022)[7] who reported low HPV coverage of 22% in the two doses in Uganda. Another study done byOluwole et al (2019)…”
supporting
confidence: 93%
“…This means the two Sub-Counties are way below the National target (80%). These findings are consistent with that found by Aruho et al (2022)[7] who reported low HPV coverage of 22% in the two doses in Uganda. Another study done byOluwole et al (2019)…”
supporting
confidence: 93%
“…From a total of 16 studies included in the final analysis, we found that five of the studies were from Nigeria. 19–23 Eight (four each) of the studies were from Ethiopia 24–27 and Uganda, 28–31 while two were from Kenya. 32 , 33 One study reported was from Cameroon 34 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled estimate of vaccination uptake of at least one dose of HPV vaccine among adolescents in Ethiopia was 55% (95%CI: 53–57), which is quite low and represents the wide gap that needs to be bridged before achieving the WHO strategy of having 90% of girls fully vaccinated by the age of 15 years in 2030 [ 6 ]. Our finding suggests that a significant proportion of adolescent girls remain largely unprotected [ 20 , 21 ]. According to the WHO recommendation, the strategy to eliminate cervical cancer requires fully vaccinating 90% of girls by 15 years of age, screening 70% of women with a high-performance test by 35 years of age and again at 45 years of age, and 90% of women identified with cervical disease receiving treatment [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…By the middle of 2020, 15 to 20% of adolescent girls took at least one dosage globally in terms of coverage. As a result, many girls who reside in nations that have not yet incorporated the HPV vaccine into their national immunization schedules are unprotected [ 20 24 ].…”
Section: Discussionmentioning
confidence: 99%